Maternity Waiting Home Interventions as a Strategy for Improving Birth Outcomes: A Scoping Review and Meta-Analysis - Samantha Smith; Hannah Henrikson; Rita Thapa; Suresh Tamang; Ruma Rajbhandari (Ubiquity Press, 2022)
Background and Objective: Over 300 000 women worldwide die due to pregnancy-related complications annually, with most occurring in developing countries where access to skilled obstetric care is limited. Maternity waiting homes (MWHs) are one intervention designed to increase access to skilled prenatal care in resource-limited settings. MWHs are defined as accommodations at or near a health facility where pregnant women can stay in the final weeks of their pregnancy so they can be easily transferred to the health facility to give birth. While MWHs have existed for decades, evidence regarding their effectiveness in reducing adverse birth outcomes has been mixed. The objective of this study is to comprehensively assess all available MWH research reporting quantitative maternal and childbirth data to determine whether MWHs are an effective maternal health strategy in resource-limited settings. Methodology: We conducted a scoping review and meta-analysis of existing literature on MWHs according to PRISMA guidelines. Descriptive statistics and odds ratios were calculated for the following birth outcomes: maternal mortality, perinatal mortality, and caesarian section. Quantitative analysis was conducted in RStudio and Stata Version 16. Results: One hundred seventy-one records were retrieved from our initial database search, of which 66 were identified as relevant. Only 15 of these records reported quantitative data on the health outcomes of interest and therefore met inclusion criteria for our meta-analysis. All studies reporting maternal mortality demonstrated a protective effect of MWHs (aggregate OR: 0.19 [0.10, 0.40]), as did all studies reporting perinatal mortality (aggregate OR: 0.29 [0.16, 0.53]). Studies reporting caesarian section were more varied and indicated less of a protective effect (aggregate OR: 1.80 [1.18, 2.75]). Conclusions: There is some indication that MWHs are an effective strategy for reducing maternal and perinatal mortality in resource-limited settings. However, our analysis was constrained by the observational design of most prior MWH studies. More rigorous MWH evaluations, ideally in the form of randomized-control trials, are needed to better determine MWH effectiveness.